Obstructive shock secondary to an unusual cause: primary cardiac lymphoma - Gregoire Ottavy; Laurent Camous; Claire Fieschi; Lucas Della Torre; Jean-David Pommier (Journal of Cardiothoracic Surgery)
Abstract Background The medico-surgical management of cardiac tumors when there is a suspicion of malignancy is complex. Moreover, in a critically ill setting, the choice of diagnostic tools seems crucial. Case presentation We present the case of a sixty-four-year-old patient with no prior medical history who was admitted to the intensive care unit with obstructive shock secondary to a right heart mass and pulmonary embolism. Clinical and biological features revealed secondary hemophagocytic lympho-histiocytosis (HLH). The patient underwent a diagnostic procedure with dual thoracoscopic and mediastinoscopy with biopsies. Following the diagnosis of primary cardiac lymphoma, the patient received sequential chemotherapy without undergoing cardiac surgery leading to initial improvement, with reductions in intracardiac obstruction and in biomarkers associated with hemophagocytic lympho-histiocytosis. Conclusion When a cardiac mass is associated with extracardiac symptoms indicative of a hematological malignancy, the preferred treatment is chemotherapy, and cardiac surgery should be avoided.